2018
DOI: 10.1017/s0007114518003197
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphataemia in severe acute malnutrition: a prospective observational study

Abstract: Severe acute malnutrition (SAM) is a major cause of child mortality and morbidity. Children treated for SAM are at risk of refeeding hypophosphataemia (HP). The study was done to find out the incidence and various predictors of moderate/severe HP in SAM among North Indian children. This prospective observational study was conducted from August 2014 to July 2015 in the inpatients’ department of Department of Paediatrics at King George’s Medical University, Lucknow, Uttar Pradesh, North India, a tertiary care te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
3
4
2
1
Order By: Relevance
“…Prevalence of hypophosphatemia in our study was 25%, 23.3% and 8.3% on admission, during transition and at discharge, respectively. The prevalence on admission was comparable with studies by Namusoke et al (37%) and Dakshayani et al (17%) [5,8], while Kimutai et al (86%), Hother et al (93%) and Chanchal et al (60%) reported very high prevalence [3,4,7]. Higher prevalence in the study by Kimutai et al could be explained by difference in study population as they enrolled only children with edematous malnutrition.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Prevalence of hypophosphatemia in our study was 25%, 23.3% and 8.3% on admission, during transition and at discharge, respectively. The prevalence on admission was comparable with studies by Namusoke et al (37%) and Dakshayani et al (17%) [5,8], while Kimutai et al (86%), Hother et al (93%) and Chanchal et al (60%) reported very high prevalence [3,4,7]. Higher prevalence in the study by Kimutai et al could be explained by difference in study population as they enrolled only children with edematous malnutrition.…”
Section: Discussionsupporting
confidence: 83%
“…Other studies reported mean serum phosphate levels lesser than 4 mg/dL on admission and transition. Also, the level usually fell from admission for first few days, as starter diet contains limited phosphate before it rises once catch-up diet with more phosphate is introduced [3,7]. Mean serum phosphate at discharge was comparable to studies done by Namusoke et al [5], but overall mean increase of 0.75 mg/dL in our study was less than 2.07 mg/dL reported by Namusoke et al…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Serum phosphate levels have been identified as strong predictors on clinical outcomes, including hospital mortality [4]. While hypophosphatemia is shown to be independently associated with increased mortality among critically ill patients, malnourished individuals, and patients with sepsis [5][6][7], hyperphosphatemia is associated with poor clinical outcomes including mortality in chronic kidney disease (CKD) [8,9], hemodialysis [10,11], acute coronary syndrome [12], and general patient population [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have focused on the impact of serum phosphate disorders (hypophosphatemia and hyperphosphatemia) [5][6][7][13][14][15][16][17], knowledge about the significance of changes in serum phosphate level and allcause mortality remains scarce. Among patients on maintenance hemodialysis, a recent study demonstrated that high variability of serum phosphate was independently correlated with increased all-cause and cardiovascular mortality, while stable serum phosphate levels and low serum phosphate variability were associated with reduced patient mortality [10].…”
Section: Introductionmentioning
confidence: 99%